Large-scale analysis of the relationship between CYP11A promoter variation, polycystic ovarian syndrome, and serum testosterone. - Gaasenbeek, M; Powell, B; Sovio, U; Haddad, L; Gharani, N; Bennett, A; Groves, C; Rush, K; Goh, M; Conway, G; Ruokonen, A; Martikainen, H; et al. (2004)
CYP11A, the gene encoding p450scc, a key enzyme in steroid biosynthesis, is a strong biological candidate for polycystic ovary syndrome (PCOS) susceptibility. Four of the five published studies that have examined CYP11A for evidence of linkage and/or association have reported significant relationships with polycystic ovary (PCO) status and/or serum testosterone levels. However, study sizes have been modest, and the current study aimed to reevaluate these findings using significantly larger clinical resources. A pair of CYP11A promoter microsatellites, including the pentanucleotide (D15S520) previously implicated in trait susceptibility, were genotyped in 371 PCOS patients of United Kingdom origin, using both case-control and family-based association methods, and in 1589 women from a population-based birth cohort from Finland characterized for PCO symptomatology and testosterone levels. Although nominally significant differences in allele and genotype frequencies at both loci were observed in the United Kingdom case-control study (for example, an excess of the pentanucleotide four-repeat allele in cases, P = 0.005), these findings were not substantiated in the other analyses, and no discernable relationship was seen between variation at these loci and serum testosterone levels. These studies indicate that the strength of, and indeed the existence of, associations between CYP11A promoter variation and androgen-related phenotypes has been substantially overestimated in previous studies.